Immediate skin-to-skin contact for low birth weight infants is safe in terms of cardiorespiratory stability in limited-resource settings - Agnes Linnér; Björn Westrup; Siren Rettedal; Kondwani Kawaza; Helga Naburi; Sam Newton; Barak Morgan; Harish Chellani; Sugandha Arya; Vincent Samuel Phiri; Ebunoluwa Adejuyigbe; Naana A.Wireko Brobby; et al. (Elsevier, 2023)
Aim: To investigate the safety of skin-to-skin contact initiated immediately after birth on cardiorespiratory parameters in unstable low birth weight infants. Methods: A randomized clinical trial was conducted in tertiary newborn units in Ghana, India, Malawi, Nigeria and Tanzania in 2017-2020, in infants with birth weight 1.0-1.799 kg. The intervention was Kangaroo mother care initiated immediately after birth and continued until discharge compared to conventional care with Kangaroo mother care initiated after meeting stability criteria. The results of the primary study showed that immediate Kangaroo mother care reduced neonatal mortality by 25% and the results have been published previously. The post-hoc outcomes of this study were mean heart rate, respiratory rate, oxygen saturation during the first four days and the need of respiratory support. Results: 1,602 infants were allocated to control and 1,609 to intervention. Mean birth weight was 1.5 kg (SD 0.2) and mean gestational age was 32.6 weeks (SD 2.9). Infants in the control group had a mean heart rate 1.4 beats per minute higher (95% CI -0.3-3.1, p = 0.097), a mean respiratory rate 0.4 breaths per minute higher (-0.7-1.5, p = 0.48) and a mean oxygen saturation 0.3% higher (95% CI -0.1-0.7, p = 0.14) than infants in the intervention group. Conclusion: There were no significant differences in cardiorespiratory parameters during the first four postnatal days. Skin-to-skin contact starting immediately after birth is safe in low birth weight infants in limited-resource settings.